Dual-envelop-oriented moving horizon path tracking control for fully automated vehicles - Guo, Hongyan; Liu, Jun; Cao, Dongpu; Chen, Hong; Yu, Ru; Lv, Chen (Elsevier, 2017)
A novel description of dual-envelop-oriented path tracking issue is presented for fully automated vehicles which considers shape of vehicle as inner-envelop (I-ENV) and feasible road region as outer-envelop (O-ENV). Then implicit linear model predictive control (MPC) approach is proposed to design moving horizon path tracking controller in order to solve the situations that may cause collision and run out of road in traditional path tracking method. The proposed MPC controller employed varied sample time and varied prediction horizon and could deal with modelling error effectively. In order to specify the effectiveness of the proposed dual-envelop-oriented moving horizon path tracking method, veDYNA-Simulink joint simulations in different running conditions are carried out. The results illustrate that the proposed path tracking scheme performs well in tracking the desired path, and could increase path tracking precision effectively.
Keywords: Fully automated vehicles; Path tracking; Model predictive control; Outer-envelop; Inner-envelop